2018
DOI: 10.1002/ldr.2959
|View full text |Cite
|
Sign up to set email alerts
|

Excessive pruning and limited regeneration: Are Faidherbia albida parklands heading for extinction in the Central Rift Valley of Ethiopia?

Abstract: Scattered Faidherbia albida trees provide multiple ecological and production benefits across the Sahel. The intensive management and use of this important tree may impede its regeneration. Regeneration bottlenecks were explored and population dynamics modelled. On experimental plots in which seed of F. albida was sown, exposure to the first 2 months of dry season resulted in a quarter of seedling mortality. Exposure to season‐long free grazing and browsing caused significantly greater seedling mortality. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…The perceptible consequences of this method are often the death of trees and a reduction in seed production during several years with corollary on the regeneration of the species. When tree branches are pruned, they could take some few years to have new fruiting branches (Sida et al 2018). Therefore, pruning was considered as strong pressure on species compared to fruit gathering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perceptible consequences of this method are often the death of trees and a reduction in seed production during several years with corollary on the regeneration of the species. When tree branches are pruned, they could take some few years to have new fruiting branches (Sida et al 2018). Therefore, pruning was considered as strong pressure on species compared to fruit gathering.…”
Section: Discussionmentioning
confidence: 99%
“…and Afzelia africana Smith ex Pers. have shown that intensive and frequent pruning of branches for forage harvesting reduce their fruit production and seed availability for seedlings recruitment (Gaoué & Ticktin 2007, Nacoulma et al 2016, Sida et al 2018.…”
Section: Harvesting Methods Used and People Perception On Their Impact On Speciesmentioning
confidence: 99%
“…Furthermore, the significant differences observed in the average age of the parklands between the three climatic zones could be explained by the creation of new F. albida parklands in Sudanian zone (Traoré et al 2020). However, (Sida et al 2018) found that in F. albida parklands in Ethiopia, a large number of individuals are older than 25 years. Ageing of the parklands in climatic zones is based on the poor management of these plant formations which hardly experience any rest (fallow).…”
Section: Woody Species Structure Of F Albida Parklandsmentioning
confidence: 96%
“…1) DBH represents the diameter at breast height. Age of each individual calculated in years was used to calculate the average age of F. albida stands in each climatic zone (Sida et al 2018).…”
mentioning
confidence: 99%
“…Oxisols are formed through weathering, humification and pedoturbation by animals while lithosols are thin soils consisting mainly of partially weathered rocks. Sida et al (2018) also characterize the soils under FMNR in central rift valley of Ethiopia as andosols, which are highly porous dark-colored soils of volcanic origin. This indicates that FMNR is mainly practiced in areas with low soil fertility which are sandy textured with a partially formed surface horizon, high permeability and low top-soil organic carbon and other nutrient contents (Larwanou et al, 2010;Haglund et al, 2011;Sendzimir et al, 2011;Moustapha et al, 2014).…”
Section: The Contexts In Which Fmnr Is Practiced Ecological Conditionsmentioning
confidence: 99%